Effects of nicotinamide riboside in ovo feeding on high-yield broiler performance, meat quality, and myopathy incidence - Maynard, Clay J.; Gonzalez, John M.; Haginouchi, Taketo; Ellis, Olivia G.; Jackson, Ashunti R.; Owens, Casey M. (Frontiers in Physiology, 2024)
Introduction: The objective of this study was to examine the effects of in ovo nicotinamide riboside (NR) feeding on high-yield broiler growth and meat quality. Methods: Fertilized Cobb 700 by-product eggs (N = 3,240) were randomly assigned to one of four in ovo treatments and injected with 0 (0NR), 250 (250NR), 500 (500NR), or 1,000 (1,000NR) mM NR at incubation-day 10. Chicks were hatched, vent sexed, and randomly placed 18 per pen in one of 32 floor pens. On day 48, birds were processed and deboned. Results: There were dose effects for all part weights (p < 0.05). Pectoralis major weight of 250, 500, and 1,000NR carcasses were heavier than 0NR (p < 0.03) but did not differ from remaining NR doses (p > 0.26). Pectoralis minor weight of 250NR carcasses was greater (p < 0.01) than 0NR and did not differ from other NR tenders (p > 0.21). Pectoralis minor weight of 500 and 1,000NR carcasses was greater than 0NR (p < 0.09), but did not differ (P = 0.82) from each other. There were no dose effects for all Pectoralis major and minor myopathy scores and incidence except incidence of tenders scoring “0” and “1” for woody-like tender. Percentage of NR1,000 tenders scoring 0 and 1 for woody-like tender were less than and greater than all other treatments, respectively (p < 0.05). There were no differences among remaining NR doses and NR0 tenders (p > 0.10). There were dose effects for muscle fiber number (P = 0.03). There tended to be more muscle fibers within 250 and 1,000NR muscles compared to 0NR (p < 0.09). Pectoralis major muscle from 500NR did not differ in muscle fiber number compared to 250 and 1,000NR (p > 0.18), but had more (p < 0.01) fibers than 0NR muscle. There tended to be more fibers in 250 and 1,000NR muscles compared to 0NR muscle (p < 0.09). Discussion: Nicotinamide riboside in ovo feeding caused birds to produce heavier parts; however, myopathy scores and incidence were minimally affected which may have been due greater muscle fiber number.